Fighting Pressures: Successful Psychosocial Adjustment of Middle Eastern Students at US Universities - Al Abiky, Waleed B. (Frontiers in Psychology, 2021)
Middle Eastern students seeking academic degrees in the US universities often experienced array of challenges in multiple levels as they adjust to the new environments. The current study investigated some of the psychosocial factors affecting their adjustments namely: age, gender and marital status. Quantitative method was used to collect data in which a survey was distributed and later analyzed for 92 Middle Eastern participants. The results of the study reveal the followings: 1) age was a significant factor impacting the level of adjustment at α.0001, 2) gender on the other hand was not statistically significant as there was no difference between males versus females on the level of adjustment, 3) results also revealed that marital status had a statistically significant impact in which married participants displayed a higher level of adjustment than singles, and 4) with the current changes in the social lives and gender roles in the Middle East, further investigations are opened for exploration.